Physico-chemical influence on the diversity of phytoplankton at Putrajaya Lake and Wetlands, Putrajaya, Malaysia - Mohd. Sabkie, Nur Syafiqah; Zulkifly, Shahrizim; Rosli, Nur Syuhada; Mat Lazim, Nurul Najwa Farihah; Yong, Christina Seok Yien (Malaysian Nature Society, 2020)
This study was conducted to determine the influence of physico-chemical parameters to the distribution and succession of phytoplanktons of Putrajaya Lake and wetlands. Water sampling was conducted at three selected sampling sites (water input: Site 1, natural remediation; Site 2 and lake activity centre: Site 3) from November 2017 to January 2018, and the physico-chemical parameters measured. Paleontological Statistics (PAST) software was used to analyse the diversity of phytoplanktons with the Shannon-Wiener index and Simpson index. Pearson Correlation, Principal Component Analysis (PCA) and Canonical Component Analysis (CCA) were also conducted to determine the relationship between phytoplankton and physico-chemical parameters at all sites. A total of 14 genera belonging to eight classes of phytoplanktons was found with Scenedesmus sp., Staurastrum sp. and Peridinium sp. being the most abundant. It was recorded that Staurastrum sp. was most correlated with ammonia and light intensity, Scenedesmus sp., correlated with nitrate, salinity, and phosphate at Site 2 in December 2017, whereas Peridinium sp. had a correlation with pH at Site 3 in January 2018. Based on this research, the diversity of the phytoplankton species and their dominance are considered as indicators of the trophic level and water quality of the sites. Thus, Site 1 and Site 2 showed a meso-eutrophic condition, while Site 3 showed a mesotrophic condition. Trophic conditions of a lake can be improved in the future with specific monitoring and management in order to maintain its functions and esthetic values.